Development process for intelligent user interfaces: an initial approach - Gonçalves, Taisa Guidini; da Rocha, Ana Regina Cavalcanti (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS), 2019)
The human-computer interaction (HCI) is a research field that supports the user interface development. Furthermore, HCI influences the intelligent user interface (IUI) area. IUI is a user interface that uses intelligent technology to reach the communication between humans and machines. The construction of IUI is not easy and requires the knowledge of different methods, techniques and technologies from many domains (such as, HCI, artificial intelligence, ergonomics, software engineering, etc.). In this way, the existence of a process is an important tool for IUI developers. The literature presents design processes and frameworks for user interface, but most of them do not offer any knowledge regarding the methods, techniques, and technologies that can be used to support the activities involved. Thus, this work proposes a development process for IUIs which offers recommendations about methods, techniques, and technologies. We hope that this process will help analysts and designers who work in IUI area.